Global Tracking Control of Quadrotor VTOL Aircraft in Three Dimensional Space - Do, Khac Duc; Paxman, Jonathan (Engineers Australia, IEEE, 2013)
This paper presents a new method for the design of controllers for quadrotor vertical take-off and landing (VTOL) aircraft which globally asymptotically track reference trajectories in three dimensional space. Roll and pitch angles plus the total thrust are considered immediate controls to track references in position and yaw angle of the aircraft. The control design is based on the newly introduced one-step ahead backstepping, standard backstepping and Lyapunov's direct methods. A combination of Euler angles and unit-quaternions are used to represent the aircraft attitude and angular velocities. The results are illustrated with simulations.